Intermittent stirring-mediated solids retention time–hydraulic retention time decoupling enhances side-stream enhanced biological phosphorus removal performance and microbial selection - Yanzhe Gong; Dongqi Wang; Wengui Gu; Ruoyu Wu; Guangxiang Duan; Jiayu Bi; Xiaopeng Qiu; Yuan Guo; Yishan Lin; Hongfang Sun; Xi Wen; Chenxin Tang; et al. (Journal of Environmental Chemical Engineering, 2026)

A study of the taxonomic status of a new tropical artificial island soil - Suping LIU; Shanquan LI; Xiaolin SUN; Faming WANG; Hongfang LU; Dongming LIU; Linhua WANG; Senhao WANG; Yongbiao LIN; Lulu ZHANG; Guoming QIN; Huaxing LI; et al. (Pedosphere, 2026)

Dual-readout lateral flow immunoassay for detection of amphenicols using intensified colorimetric–fluorescent carbon dots nanocomposite - Hongfang Li; Wenqing Xu; Yina Zhu; Hongxing Wei; Xiaoyue Liu; Lin Li; Guoliang Li (Food Chemistry, 2025)

Optimizing multiple ecosystem services in Eucalyptus plantations: Dual effects of intercropping and restoration - Lei Zhang; Siyu Liu; Yanjia Wang; Fangwei Zhang; Qiuyu Luo; Yongbiao Lin; Dafeng Hui; Shenglei Fu; Jun Wang; Zhanfeng Liu; Ruoyi Lin; Hai Ren; et al. (Journal of Cleaner Production, 2024)

In situ visualization of polycyclic aromatic hydrocarbon hydrothermal decomposition process utilizing planar induced fluorescence: A mechanistic analysis - Xiangjin Meng; Hongchao Dai; Wenjun Lin; Hongfang Liu; Xingang Qi; Xiao Cai; Jinhua Wang; Zuohua Huang; Hui Jin; Liejin Guo (Chemical Engineering Journal, 2024)

Long-term species-level observations indicate the critical role of soil moisture in regulating China's grassland productivity relative to phenological and climatic factors - Shuai An; Xiaoqiu Chen; Fangjun Li; Xuhui Wang; Miaogen Shen; Xiangzhong Luo; Shilong Ren; Hongfang Zhao; Yan Li; Lin Xu (Science of The Total Environment, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

A facile fluorescence microplate immunoassay based on an in situ fluorogenic reaction for the detection of two highly toxic anticoagulant rodenticides in food and biological matrix - Hongfang Li; Jie Chen; Wenqing Xu; Baowei Huang; Chuanyi Peng; Huimei Cai; Ruyan Hou; Kai Wen; Lin Li; Baolei Dong; Zhanhui Wang (Food Chemistry, 2024)

Multi‐ecosystem services differently affected by over‐canopy and understory nitrogen additions in a typical subtropical forest - Yang Tian; Peng Zhou; Lang Zhou; Lei Zhang; Yongbiao Lin; Yanjia Wang; Jun Wang; Dafeng Hui; Hai Ren; Hongfang Lu (Global Change Biology, 2024)
Obtaining a holistic understanding of the impacts of atmospheric nitrogen deposition on multiple ecosystem services of forest is essential for developing comprehensive and sustainable strategies, particularly in heavy N deposition regions such as subtropical China. However, such impacts remain incompletely understood, with most previous studies focus on individual ecosystem function or service via understory N addition experiments. To address this knowledge gap, we quantified the effects of over‐canopy and understory N additions on multiple ecosystem services based on a 7‐year large‐scale field experiment in a typical subtropical forest. Our results showed continued over‐canopy N addition with 50 kg ha −1 year −1 over a period of 4–7 years significantly increased plant nutrient retention, but did not affect the services of soil nutrient accumulation, water yield, C sequestration (in plants and soil), or oxygen release. There were trade‐offs between the soil and plant on providing the services of nutrient accumulation/retention and C sequestration under over‐canopy N addition. However, without uptake and retention of tree canopy, the trade‐off between soil and plant were more weaken under the understory N addition with 50 kg ha −1 year −1 , and their relationships were even synergetic under the understory N addition with 25 kg ha −1 year −1 . The results suggest that understory N addition cannot accurately simulate the effects of atmospheric N deposition on multiple services, along with mutual relationships. Interestingly, the services of plant N, P retention, and C sequestration exhibited a synergetic increase under the over‐canopy N addition but a decrease under the understory N addition. Our results also found tree layer plays a primary role in providing plant nutrient retention service and is sensitive to atmospheric N deposition. Further studies are needed to investigate the generalized effects of forest canopy processes on alleviating the threaten of global change factors in different forest ecosystems.

Residue and intake risk assessment of prothioconazole and its metabolite prothioconazole-desthio in wheat field - HongFang Lin; Bizhang Dong; JiYe Hu (Environmental Monitoring and Assessment, 2017)

Gymnocypris przewalskii decreases cytosolic carbonic anhydrase expression to compensate for respiratory alkalosis and osmoregulation in the saline-alkaline lake Qinghai - Zongli Yao; Wenfei Guo; Qifang Lai; Jianquan Shi; Kai Zhou; Hongfang Qi; Tingting Lin; Ziniu Li; Hui Wang (Journal of Comparative Physiology B, 2016)

Vegetative Ecological Characteristics of Restored Reed (Phragmites australis) Wetlands in the Yellow River Delta, China - Xuehong Wang; Junbao Yu; Di Zhou; Hongfang Dong; Yunzhao Li; Qianxin Lin; Bo Guan; Yongli Wang (Environmental Management, 2012)